2011
DOI: 10.1097/prs.0b013e3181f958de
|View full text |Cite
|
Sign up to set email alerts
|

Are Patients Making High-Quality Decisions about Breast Reconstruction after Mastectomy? [Outcomes Article]

Abstract: Background Variation in rates of breast reconstruction after mastectomy has raised concerns about the quality of decisions about reconstruction. We sought to evaluate patient decision making about reconstruction, using a validated measure of knowledge and preferences related to reconstruction. Methods A cross-sectional survey of early-stage breast cancer survivors from four university medical centers was conducted. The survey included measures of knowledge about specific reconstruction facts, personal goals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 23 publications
1
47
0
1
Order By: Relevance
“…Surveys of women after breast reconstruction have found women feel strongly about having a natural appearance in clothing and are motivated by the idea of improving their body image. 11,27,28 We similarly found women to be more motivated by body image than sexual relations or concerns of femininity. In fact, only 20% of women reported being worried about their relationship or their sexual relations if they did not choose breast reconstruction.…”
Section: Why Patients Choose Breast Reconstructionsupporting
confidence: 56%
“…Surveys of women after breast reconstruction have found women feel strongly about having a natural appearance in clothing and are motivated by the idea of improving their body image. 11,27,28 We similarly found women to be more motivated by body image than sexual relations or concerns of femininity. In fact, only 20% of women reported being worried about their relationship or their sexual relations if they did not choose breast reconstruction.…”
Section: Why Patients Choose Breast Reconstructionsupporting
confidence: 56%
“…19 We do not support this assessment. We think that the group of patients who are open for BR will be given the opportunity to talk about their needs during their follow-up (in our study cohort, the vast majority of patients reported that they received information regarding BR, both preoperatively and during aftercare.).…”
Section: Different Attitudes Of Patients Who Had Mastectomy Towards Bmentioning
confidence: 59%
“…In our prior retrospective study, which also used the Decision Quality Instrument, overall knowledge about reconstruction 2.5 years after mastectomy was 37.9%. 13 Knowledge about breast cancer surgery (mastectomy versus breast conserving surgery) has also been limited in prior studies, with patients correctly answering about half of questions about the pros and cons of surgery. 1416 Patients also have incomplete knowledge about systemic therapy, with frequent overestimation of the survival benefit of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In our prior retrospective study, knowledge about complication risk was even lower, at 3%. 13 The DQI question on complication risk was developed using the best available evidence about long-term complications of reconstruction. 13, 19 That evidence has found complication rates in the range of 20–33%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation